Draft Revised Code of Good Practices on Fiscal Transparency. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The IMF is in the process of revising its 2001 Code of Good Practices on Fiscal Transparency. The four core principles of the original Code remain unchanged in the revision: institutional clarity, open budget processes, public information and integrity. However, the document has been updated and broadened to reflect recent developments and practices. The IMF is requesting public comment on the proposed revised Code. The deadline for comments is November 17, 2006.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet